Effectiveness of expanded clay as a bacteria carrier for self-healing concrete - Han, Sanghyun; Choi, Eun Kyung; Park, Woojun; Yi, Chongku; Chung, Namhyun (Applied biological chemistry, 2019)
Cracking of concrete over time, is a natural phenomenon. Longer service life of concrete structures is desirable. Self-healing concrete using bacteria, which could form CaCO 3 crystals for crack sealing, has promised benefits to reduce cost for concrete maintenance, because cracks could be autonomously repaired without human intervention. However, because of harsh concrete internal environment render the effectiveness depending on the bacteria viability within concrete. In this study, expanded clay (EC) was used as a carrier, to protect bacteria ( Lysinibacillus boronitolerans YS11) from the harsh environment during the process. Existence of bacteria inside EC was observed using electron microscopy. When exposed to bacterial solution of 1.0 × 10 9 cells/mL, bacterial density within EC reached approximately 0.82 × 10 7 cells/g of dry EC. Extent of bacterial viability within EC, submerged to solution containing 1.0 × 10 8 cells/mL, was 53.6% of free bacteria solution containing 1.0 × 10 7 cells/mL, as measured with fluorescein diacetate assay. When rate of calcium carbonate formation was measured with Ca 2+ disappearance, rates were comparable between bacteria within EC (submerged to bacterial solution containing 1.0 × 10 8 cells/mL) and free bacteria (1.0 × 10 7 cells/mL). This finding indicates that bacteria with EC is very active for generation of CaCO 3 within EC. All experimental results suggest that EC may be an adequate bacteria carrier for self-healing concrete.